2021
DOI: 10.1080/03031853.2021.1971097
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19 on black farmers in South Africa

Abstract: Covid-19 is impacting on food systems and food security around the world, including in South Africa, revealed most starkly in rising food prices and increasing food insecurity. Debates on what kind of food system we need to respond to this crisis remain unresolved and lacking in a good understanding of the impacts of Covid-19 on farmers who are key actors in food systems. This article contributes to these debates by revealing the experiences of black fresh produce farmers in South Africa since Covid-19 arrived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…While only two points were given concerning impacts to women, they were related to loss of employment and therefore a critical component of food security (e.g., Nigerian fish businesses went from supporting 20% to 2% female employment between February—pre-pandemic and April; however, males were also impacted, but to a lesser extent, with total man workers dropping to 20% from 50% during same period). In South Africa, interviews ( n = 40; women = 22, men = 18) provided insight into women vs. men farmers [ 29 ]. While in general there were no formal reports about differences in gender, the study found that only women farmers lost access to land ( n = 2), and five out of six farmers who had to halt production completely were women (two women farmers voluntarily stopped work to stay at home to care for family).…”
Section: Resultsmentioning
confidence: 99%
“…While only two points were given concerning impacts to women, they were related to loss of employment and therefore a critical component of food security (e.g., Nigerian fish businesses went from supporting 20% to 2% female employment between February—pre-pandemic and April; however, males were also impacted, but to a lesser extent, with total man workers dropping to 20% from 50% during same period). In South Africa, interviews ( n = 40; women = 22, men = 18) provided insight into women vs. men farmers [ 29 ]. While in general there were no formal reports about differences in gender, the study found that only women farmers lost access to land ( n = 2), and five out of six farmers who had to halt production completely were women (two women farmers voluntarily stopped work to stay at home to care for family).…”
Section: Resultsmentioning
confidence: 99%
“…Problems in the production and sale of agricultural products have an impact on the condition of farmers both in terms of finance, family and health. The results of other studies also found that farmers experienced many challenges due to the COVID-19 pandemic and did not get optimal support from the government (Nchanjia & Lutomia, 2021;Wegerif, 2021). Five studies (Bossenbroek & Ftouhi, 2021;Jaacks et al, 2021;Kulkarni et al, 2021;Landry et al, 2021;Lusk & Chandra, 2021) described about farmers on their social life from the production process (inputs, harvest and sell), accessing incentives, finding workers and lower income with high risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the US found that the farmers were at higher risk of contracting COVID-19 ( 38 ). This has led to a reduction in farm produce across the world ( 39 , 40 ). This is difficult to ascertain in Bhutan due to a lack of data.…”
Section: Discussionmentioning
confidence: 99%